ANALYSIS OF THE IMPLEMENTATION OF THE PARTNERSHIP POLICY BETWEEN SUPERMARKETS AND SIDOARJO SMES IN THE STORE REVIEW PROGRAM - Miftakhul Huda, Ary (MAP Observer: Jurnal Penelitian Administrasi Publik, 2025)
This study aims to identify and analyze the determining factors in the implementation of the partnership policy between supermarkets and Sidoarjo's SMEs in the Bedah Warung Program. These factors need to be optimized in developing the implementation of the partnership policy between supermarkets and Sidoarjo's SMEs in the Bedah Warung Program in the future. The theory used by Knill and Tosun in Rahardian (2020) states that the factors of effectiveness in policy implementation are: Choice of Policy Instruments; Precision and Clarity of Policy Design; Control Structures; Institutional Design; Administrative Capacities; and Social Acceptance. The research method used is a descriptive research method with a case study design. The results of the study indicate that the determining factors in the implementation of the partnership policy between supermarkets and Sidoarjo's SMEs in the Bedah Warung Program are the choice of policy instruments, the accuracy and clarity of policy design, administrative capacity, and social acceptance. The Sidoarjo Regency Industry and Trade Office has established a clear legal basis in the Peraturan Daerah Kabupaten Sidoarjo Nomor 10 Tahun 2019 concerning the Arrangement of Supermarkets in Sidoarjo Regency. Factors that need to be optimized in developing the implementation of the Supermarket-SME partnership policy under the Bedah Warung Program are the control structure and institutional design. Although the Peraturan Daerah Kabupaten Sidoarjo Nomor 10 Tahun 2019 has been established, control and supervision are still suboptimal. Furthermore, there is a lack of technical coordination with government organizations tasked with overseeing the partnership.